Recent developments in model-based fault detection and diagnostics of gas pipelines under transient conditions - Syed, M.M. (Elsevier B.V., 2020)
Gas pipelines are prone to faults due to aging, corrosion, and external factors. Undetected faults can result in injuries, damage to properties, and environmental contamination. Several techniques have been developed to help detect faults, though each technique having pros and cons. This review is set out to identify research gaps related to fault detection and diagnostics under transient conditions and associated inputs for a robust design. A closer look at the available literature reveals that there is indeed more research required in terms of addressing pipeline-compressor-valve system, multiple fault scenario, uncertainty quantification, and multiphase condition. Â© 2020 Elsevier B.V.